2013
DOI: 10.4314/ajpsy.v16i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Emotional distress among caregivers of patients with epilepsy in Katsina State, Northern Nigeria

Abstract: The study demonstrated a high level of emotional distress associated with caring for patients with epilepsy, which is comparable to other studies carried out in other parts of the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 17 publications
1
23
1
Order By: Relevance
“…Caregivers are people who take care of others, often parents, spouse, or children with special medical needs or disability and they play an important role in the management of patients with epilepsy [ 1 – 3 ]. Caregiving is a broad responsibility, including not only practical help and care but also emotional support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers are people who take care of others, often parents, spouse, or children with special medical needs or disability and they play an important role in the management of patients with epilepsy [ 1 – 3 ]. Caregiving is a broad responsibility, including not only practical help and care but also emotional support.…”
Section: Introductionmentioning
confidence: 99%
“…Mental illness influences not only the primary individuals having the diagnosis but also families, friends, and important others around them [ 6 ]. Mental distress among caregivers manifests itself with different levels of depression, anxiety, mood disturbances including losing of hope, feeling sad, loneliness, isolation, fearfulness, being easily bothered, nervousness, somatic symptoms such as headache, fatigue, and insomnia arising from providing care for the person in problem [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 The prevalence of emotional distress in this study was 15.5% which is relatively low when compared with the prevalence of 65.7% reported among caregivers of patients with epilepsy in the northern part of Nigeria using a similar questionnaire. 16 The prevalence of high/clinically significant parenting stress was 12.0%, and the level of parenting stress was highest for parental distress and lowest for parent-child dysfunctional interaction. Since clubfoot is a non-life threatening birth defect without any associated pain in the child's limb, some parents may not really worry.…”
Section: Discussionmentioning
confidence: 93%
“…8,13 However, research focusing on the experiences of parents/caregivers of patients with chronic diseases in the clinical setting is increasing. [16][17][18][19] This study assessed emotional distress and parenting stress associated with caring for children with clubfoot using HADS and PSI-SF in which nine (15.5%) parents reported emotional distress and seven (12.0%) had parenting stress. The majority of parents in this study were mothers and this is understandable as it is a common tradition that women are saddled with the duties of care for their children in the family.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Despite scientific advances in its diagnosis and therapy, misconceptions about its cause and treatment still exist. 9 Although seizure control is the mainstay of epilepsy treatment, patient education is critical to improve attitudes andproper coping mechanisms. 10 In the West, several studies have reported thatpeople with epilepsy (PWE) knew only a little more, and in some cases even less, about their disorder than those without epilepsy.…”
Section: -6mentioning
confidence: 99%